The Effects of Extracted Peptide from Skin of Iraqi Frog (Rana ridibunda) on Human Leukemic Lymphocytes (Baghdad Science Journal, 2019)
The purified frog skin peptides were tested on leukemic patients lymphocytes, which revealed effects of cytotoxicity. Four frogs (Rana ridibunda) were stimulated by single intra-peritoneal injection of norepinephrine-HCl . Five different peptides;1(18) A, 2(19) L, 3(20) I,4(21) E and 5(22) Y were isolated and quantified. The peptide 3(20)I had 5.87% of hemolysis, while healthy human lymphocytes cytotoxic activity was for 2(19)L with inhibition( -10.4%).All peptides were subjected to polyacrylamide gel electrophoresis. The results revealed peptides 1(18)A, 2(19)L, 3(20)I which appeared as low as 10 KDa marker. Theoretically, the whole polypeptide had a molecular weight 7488.61 Dalton and contained on 62.405 amino acid (a.a). The peptide 4(21)E had a highest inhibitory effect(46%) on tumor cell line L20B. Furthermore , peptides effects on acute and chronic myeloid lymphocytic leukemia patients cell cultures revealed peptides selectivity in their action according to their net charge and functional group as reactant proton donor by the evidence of peptide 5(22)Y, 16.22 Dalton so it was either N—terminus (--NH2) or C—terminus (--OH) that led to cross cell membrane then acted as antigen mediated and activated cells in a high significant value (-142.37± 47.69)for acute myeloid lymphocytic leukemia .Both of peptides 3(20) I and 2(19) L were revealed a highly significant differences within Chr.40 and Chr. 22 of inhibition effects by testing volumes 15 µl and 10 µl . Those inhibition effects were due to peptides reaction with mitochondrial membrane which led to apoptosis . Conclusion; Frog skin peptides have a therapeutically worth for malignant diseases. Also some of peptides were activated lymphocytes may to cure immunodeficiency.